2016
DOI: 10.1088/0957-4484/27/50/505605
|View full text |Cite
|
Sign up to set email alerts
|

Amine functionalized cubic mesoporous silica nanoparticles as an oral delivery system for curcumin bioavailability enhancement

Abstract: In the present work, a simple method was used to develop composite curcumin-amine functionalized mesoporous silica nanoparticles (MSN). The nanoparticles were used to improve the bioavailability of curcumin in mice through oral administration. We investigated the effect of particle size on the release profile, solubility and oral bioavailability of curcumin in mice, including amine functionalized mesoporous silica micron-sized-particles (MSM) and MSN (100-200 nm). Curcumin loaded within amine functionalized MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…Curcuma longa L. dry extract was purchased from and certified by Java Plants (Solo, Indonesia). C-MSN was prepared according to the method described by Hartono et al (2016). Materials for C-MSN hepatoprotective study are carbon tetrachloride (E-Merck, Germany), corn oil (PT.…”
Section: Sample and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcuma longa L. dry extract was purchased from and certified by Java Plants (Solo, Indonesia). C-MSN was prepared according to the method described by Hartono et al (2016). Materials for C-MSN hepatoprotective study are carbon tetrachloride (E-Merck, Germany), corn oil (PT.…”
Section: Sample and Chemicalsmentioning
confidence: 99%
“…Ethanol was evaporated slowly under vacuum at a temperature of 55°C. Finally, curcumin loaded MSN was obtained (Hartono et al, 2016).…”
Section: C-msn Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoporous silica nanoparticles (MSNs), exhibiting attractive properties, such as large surface area [1], easy surface modification [2,3] and multiple morphology [4], have attracted extensive attention for their application in oral drug delivery [5,6]. Recently, numerous studies have synthesized MSNs with various properties [7,8], and they demonstrated that the physical parameters of mesoporous silica materials have played an important role in both in vitro and in vivo biological performance [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme immobilization in an inorganic support, such as mesoporous silica particles (MSP), is a convenient strategy due to its low cost, high surface area, tunable particle and pore size. Moreover, the potential of MSP as oral delivery systems was previously shown for small molecules, whose release could be triggered by external stimuli (e.g., the increase in pH along the GI-tract) [17][18][19] .…”
mentioning
confidence: 94%